The physical effects of wearing personal protective equipment: a scoping review - Tume, Lyvonne N.; Ungari, Davide; Bannerman, Fariba; Cuddihy, Sean; Gnanalingham, Claire; Phillips, Hayley (International Journal of Infection Control, 2022)
Background: The COVID-19 pandemic has required healthcare workers to wear personal protective equipment (PPE), and although there is increasing awareness of the physical effects of wearing PPE, the literature has yet to be synthesised around this topic. Methods: A scoping review was conducted to synthesise existing literature on the physical effects of wearing PPE and identify gaps in the literature. A comprehensive search strategy was undertaken using five databases from 1995 to July 2020. Results: A total of 375 relevant articles were identified and screened. Twenty-three studies were included in this review. Studies were conducted across 10 countries, spanning 16 years from 2004 to 2020. Half (13/23) were randomised controlled trials or quasi-experimental studies, five surveys, two qualitative studies, two observational or case series and one Delphi study. Most (82%, 19/23) studies involved the N95 mask (either valved or unvalved). None specifically studied the filtering facepiece 3 mask. The main physical effects relate to skin irritation, pressure ulcers, fatigue, increased breathing resistance, increased carbon dioxide rebreathing, heat around the face, impaired communication and wearer reported discomfort. Few studies examined the impact of prolonged wear (akin to real life practice) on the physical effects, and different types of PPE had different effects. Conclusions: The physical effects of wearing PPE are not insignificant. Few studies examined the physiological impact of wearing respiratory protective devices for prolonged periods whilst conducting usual nursing activity. No ideal respirators for healthcare workers exist, and the development of more ergonomic designs of PPE is required.